2011
DOI: 10.1111/j.1365-2702.2010.03504.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health nursing in emergency departments: the case for a nurse practitioner role

Abstract: It is expected that those presenting with mental health issues to the emergency department will benefit through the increased assessment and management skills of staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 32 publications
0
11
0
5
Order By: Relevance
“…Bien que prometteuse, l'évaluation systématique de ses effets sur le système de santé n'en est qu'à ses débuts. Les résultats de quelques études qualitatives indiquent un degré élevé de satisfaction en regard de la disponibilité, de l'accessibilité aux services, de l'écoute, du soutien reçu, de l'information et de l'éducation à la santé (Nicholls et al, 2011 ;Wortans et al, 2006). De plus, une étude quasi expérimentale, réalisée dans un service de crise et d'intervention brève dans la communauté, visait à comparer le traitement entrepris par l'infirmière praticienne en santé mentale (évaluation, prescription, plan de traitement) au traitement usuel entrepris par le psychiatre (groupe contrôle).…”
Section: Vers Une Modernisation Du Rôle Professionnel Des Infirmièresunclassified
“…Bien que prometteuse, l'évaluation systématique de ses effets sur le système de santé n'en est qu'à ses débuts. Les résultats de quelques études qualitatives indiquent un degré élevé de satisfaction en regard de la disponibilité, de l'accessibilité aux services, de l'écoute, du soutien reçu, de l'information et de l'éducation à la santé (Nicholls et al, 2011 ;Wortans et al, 2006). De plus, une étude quasi expérimentale, réalisée dans un service de crise et d'intervention brève dans la communauté, visait à comparer le traitement entrepris par l'infirmière praticienne en santé mentale (évaluation, prescription, plan de traitement) au traitement usuel entrepris par le psychiatre (groupe contrôle).…”
Section: Vers Une Modernisation Du Rôle Professionnel Des Infirmièresunclassified
“…There is very limited literature reporting on the initial implementation of NPC roles (Masso & Thompson 2016), and this has focussed primarily on emergency departments (Nicholls et al 2011;Plath et al 2017). In mental health settings, Wortans and Happell (2006) report consumer satisfaction with NPC care provision in a crisis assessment and treatment team.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for MHNP has been explored and described in detail (Baker 2010; Elsom et al . 2005; 2007; 2009; Fisher 2005; Gardner & Gardner 2005; Nichols et al . 2011; Wand & Fisher 2006; Wand & White 2007a,b; Wortans et al .…”
Section: Introductionmentioning
confidence: 99%
“…The NP is a specialized nurse, prepared at least to Master's level, and typically works within a multidisciplinary context, providing autonomous assessment and management of clients. The potential for MHNP has been explored and described in detail (Baker 2010;Elsom et al 2005;2009;Fisher 2005;Gardner & Gardner 2005;Nichols et al 2011;Wand & Fisher 2006;Wand & White 2007a,b;Wortans et al 2006); however, there is an absence of research outcomes from services provided by MHNP. A recent census of Australian NP conducted by Gardner et al (2009) found that MHNP were the second largest group (n = 12) represented after emergency NP (n = 39).…”
Section: Introductionmentioning
confidence: 99%